Trauma without Witness: Memory and Generational Silence in Claire Fuller’s The Memory of Animals - Debarpita Naha (ILN Journal: Indian Literary Narratives, 2025)
The literature of trauma frequently depends on witnessing via testimony, recollection, and generational storytelling to maintain memory and facilitate healing. Nevertheless, Claire Fuller’s The Memory of Animals (2023) explores a distinct landscape, illustrating trauma as unobserved, unvoiced, and defiant to expression. This article investigates how such trauma interrupts narrative consistency and unravels identity. Drawing on Cathy Caruth’s theory of trauma as belated and incomprehensible, alongside Dominick LaCapra’s notions of post memory and the acting out/working through framework, the novel reveals how personal and inter generational trauma persists in silence, exposing fractures in memory, communication, and the capacity to process or transmit suffering across generations. The characters' struggles serve as a poignant reminder of the enduring impact of unresolved pain, often manifesting in their relationships and perceptions of self. The narrative challenges readers to confront the complexities of trauma, urging a deeper understanding of how it shapes both individual lives and societies.